Factors Influencing Cooperative Members' Intention In Wakaf At Kopsyah BMI Leuwiliang, Rajeg And Ciawi Branches - RH, Alhamidi Putrabana; Tanjung, Hendri; Ibdalsyah, Ibdalsyah (Al-Infaq: Jurnal Ekonomi Islam, 2024)
The aim of this study is to identify and analyze the factors influencing cooperative members' interest in waqf, specifically focusing on income, knowledge, and information media, using case studies of Kopsyah BMI branches in Leuwiliang, Rajeg, and Ciawi. The research seeks to assess the impact of these factors on waqf collection and address obstacles hindering optimal implementation. The research method used is a quantitative research method using survey analysis which aims to find out in detail. This research focuses on income, knowledge and information media factors that support waqf collection. The results of the analysis show that: (1) in the parameter estimation equation for the income variable, a z value of 2.122 is obtained and a sig value <0.05, namely 0.034, which means that there is an influence of the predictor variable. in his response. (2) The results of the probit parameter estimation test obtained a z value of 2.013 and a sig value <0.05, namely 0.044, which means that there is an influence of the predictor variables on the response. (3) The results of the probit parameter estimation test obtained a z value of 0.210 where the sig value > 0.05, namely 0.834, which means that the information media variable has no influence or relationship on waqf interest.